Clifford's manners - Bridwell, Norman (New York : Scholastic, 1987)
Everyone loves Clifford because he has good manners.
Grades K-3.
300
Keywords: Manners; Manners -- Fiction; Dogs; Courtesy -- Fiction; Dogs -- Fiction; Etiquette -- Fiction